Influence of the surface crack concentration and crack orientation in concrete subjected to a pulsed mechanical action on the electrical response parameters; Technical Physics; Vol. 59, iss. 12 - Fursa T. V. Tatyana Viktorovna (2014, 2014)
Title screen